NONLINEAR PROPERTIES OF STRUCTURAL HETEROGENEOUS PHOTONIC CRYSTAL FIBERS WITH As2Se3 SUBSTRATE - Thi Thuy Nguyen; Van Hung Dao (Tạp chí Khoa học Đại học Đà Lạt)
We examine the possibility of improving the nonlinear properties of photonic crystal fibers (PCFs) with As2Se3 substrates by creating a difference in the diameters of the air holes of the rings around the core. With the new design, all-normal dispersion properties, small effective mode area, high nonlinear coefficient, and low confinement loss were achieved in the long-wavelength range of 2.0–7.0 µm. The highest nonlinear coefficient is 4414.918 W-1.km-1 at 4.5 µm for the lattice constant (Ʌ) of 3.0 µm and the filling factor (d/Ʌ) of 0.85, while the lowest loss is 1.823´10-21 dB/cm with Ʌ = 3.5 µm and d/Ʌ = 0.8. Based on the numerical simulation results, the characteristics of two optimal structures have been analyzed in detail to guide the application in supercontinuum generation.